Effects of managerial labor market on executive compensation: Evidence from job-hopping - Gao, Huasheng; Luo, Juan; Tang, Tilan (Journal of Accounting and Economics, 2015)
We find that companies dramatically raise their incumbent executives’ pay, especially equity-based pay, after losing executives to other firms. The pay raise is larger when incumbent executives have greater employment mobility in the labor market, when companies lose senior executives, and when job-hopping executives receive favorable job offers in their new firms. A company׳s subsequent pay raise to incumbent executives after losing an executive diminishes its deficiency in executive compensation relative to its industry peer firms, and is effective at retaining its incumbent executives. Overall, our evidence suggests that executive job-hopping activity has significant effects on firms’ compensation policies.